PENGARUH JOB ENRICHMENT, REWARD DAN TEAMWORK TERHADAP EMPLOYEE ENGAGEMENT PADA PT NUSANTARA BERLIAN MOTOR - Wahyono, Teguh (Journal of Community Research and Service, 2022)
This study aims to determine the effect of Job Enrichment, Reward and Teamwork on Employee Engagement at PT Nusantara Berlian Motor. The sample in this study were all employees of PT Nusantara Berlian Motor, totaling 45 employees. This research was conducted from July to November 2020. Sources of data were collected through questionnaires. This study uses quantitative data with multiple linear regression analysis model. The results showed that Job Enrichment and Reward had a positive and significant effect on Employee Engagement at PT Nusantara Berlian Motor partially. Teamwork does not have a significant effect on Employee Engagement at PT Nusantara Berlian Motor partially. Job Enrichment, Reward, and Teamwork simultaneously have a positive and significant effect on Employee Engagement at PT Nusantara Berlian Motor. Keywords:  Job Enrichment, Reward, Teamwork, Employee Engagement